Natural Foundations for Management of Balanced Economic Development. Part I. The transition to management concepts based on the physical economy - Shevchuk, V. O. (Statistics of Ukraine, 2016)
The economic management should be considered as a component of the nature and rely upon the laws analogous to the ones of the nature. Unlike the nature with its implicit capacity to reproduce, the economy needs conscious management. The theoretical and practical framework for economic management needs to build on theoretical and applied knowledge pertaining to the needs of the economic development harmonized with the nature. The study aims to substantiate physical and economic foundations for management of economic development. Theoretical framework for the economic development strategy is studied from the perspective of the unique intellectual legacy of S. Podolynskyi, as well as V. Vernadskyi and M. Rudenko who continued and elaborated physical-economic ideas of their outstanding predecessor. The innovative results of Ukrainian scientists in physical economy, conforming to the arguments of advanced management theories, form physical-economic knowledge based on the natural principles of balanced economic development. It is concluded that the fundamental principles of nature underlying economic management in our times are (i) keeping with the law of energy conservation, and (ii) consideration for energy distinction between the living and the non-living. These fundamental scientific theses have the critical role in sustaining the economic balance and the long-term development of economic management.